Magnetic properties of one defects on borophene tri-layer structure: a Monte Carlo study. (1st November 2020) - Sahdane, T.; Masrour, R.; Jabar, A.
ABSTRACT: The effect of the one defects on borophene tri-Layer structure consisting of nineteen hexagonal B36 units of a mixed spin S (A) = 7/2, S (B) = 2 and S (C) = 1/2 was study via Monte Carlo simulation in the absence and presence of external magnetic and crystal fields. Monte Carlo simulation method with the Metropolis algorithm is used to study magnetic properties of this system. To complete this study, the hysteresis cycle is established for fixed values of defect, temperature, crystal field value exchange interactions.